Atribut Produk Wisata dalam Membangun Loyalitas Pengunjung dengan Kepuasan Pengunjung Sebagai Variabel Mediasi (Studi Pada Wisata Pantai Tlangoh Kabupaten Bangkalan) - Falahah, Nurul; Setiyarini, Triana (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This study aims to determine the influence of tourism product attributes on visitor loyalty with visitor satisfaction as a mediating variable. The method used in this research is purposive sampling, namely a sample determination technique by considering certain criteria with a sample size of 97 respondents. By using the path analysis method (path analysis). The results of this study indicate that 1) Tourism product attributes have a positive and significant effect on visitor loyalty at Tlangoh Beach Tourism. 2) Tourism product attributes have a positive and significant effect on visitor satisfaction to Tlangoh Beach Tourism. 3) Visitor satisfaction has a positive and significant effect on visitor loyalty to Tlangoh Beach Tourism. 4) Tourism product attributes have a positive and significant effect on visitor loyalty through visitor satisfaction at Tlangoh Beach Tourism.